P 46 Effects of repetitive neuromuscular magnetic stimulation targeting to the upper trapezius muscles in children with headache disorders. (May 2022) - Börner, C.; Staisch, J.; Hauser, A.; Lang, M.; Frohnmüller, M.; Hannibal, I.; Huß, K.; Kruse, S.; Klose, B.; Lechner, M.F.; Sollmann, N.; Landgraf, M.N.; et al.
Abstract : Question To assess clinical and muscular effects of a repetitive neuromuscular magnetic stimulation (rNMS) intervention targeting to the upper trapezius muscles (UTM) in pediatric patients with headache disorders. Methods A retrospective chart review resulted in 23 patients with migraine, migraine + tension-type headache (TTH), or post-traumatic headache (PTH), who received 28 rNMS interventions in a pediatric headache center. During 6 sessions, rNMS was delivered to UTM bilaterally (duration: 15min/side, frequency: 20 Hz, 7s ON-time, 10s OFF-time). Headache frequency, duration, and intensity 3 months before and after treatment were recorded using a customized standardized questionnaire prior to the first treatment and at follow-up (FU). We categorized patients into responder classes based on the relative reduction in headache frequency (≥25%, ≥50%, ≥75%). Effects on the muscular level were assessed by pressure pain thresholds (PPTs) above the UTM before, during rNMS treatment, and at FU after 4 to 20 weeks. Results Data from 20 patients were analyzed (14.10 ± 2.69 years; 60% females) as 2 patients were lost to FU and data of 1 patient was classified as outlier based on a late FU (3 SDs above mean FU time) and excluded from analysis. Compared to baseline, headache frequency (p=.017) and minimum and maximum headache intensities (p=.017; p=.023) were significantly reduced at FU. 11 patients (44%) were classified as ≥25% responders, with 7 patients (28%) experiencing a ≥75% reduction of monthly headache days. PPTs above the UTM significantly increased from baseline (left lateral: 2.00 ± 1.37, left medial: 1.96 ± 1.27, right medial: 1.83 ± 1.26, right lateral: 1.94 ± 1.37) to the last treatment session (left lateral: 3.28 ± 2.21, left medial: 3.17 ± 1.99, right medial: 3.17 ± 2.06, right lateral: 3.24 ± 2.25) (left lateral: p=.002, left medial: p=.002, right medial: p=.001, right lateral: p=.003). This increase from baseline sustains until FU (left lateral: 2.87 ± 2.11, left medial: 2.95 ± 2.11, right medial: 2.95 ± 2.11, right lateral: 2.81 ± 2.04) (left lateral: p=.047, left medial: p=.012, right medial: p=.002, right lateral: p=.028). After 14 rNMS interventions in the primary headache group, 6 patients (43%) were classified as ≥25% responders, with 2 patients (14%) experiencing a ≥75% reduction of monthly headache days. After 11 rNMS interventions in the PTH group, 5 patients (46%) were classified as ≥25% responders, with 5 patients (46%) experiencing a ≥75% reduction of monthly headache days. Conclusion Beneficial effects regarding headache characteristics and muscular PPTs were documented in pediatric patients with headache disorders. The latter having a sustained effect up to weeks to months. Based on the concept of the trigemino-cervical complex, rNMS of the UTM may act via neuromodulation of nociceptive processing at the central level.